MENGULIK SISI KETERLAMBATAN PENYERAPAN ANGGARAN - Ika Anisa Putri; Andriana Andriana; Kartika Kartika; Indah Purnamawati; Alfi Arif (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2021)
ABSTRACTThis research aims to examine and investigate in depth about the causes of the absorption of delays that occur in the Central University of Jember University. This research begins with the uneasiness of the phenomenon that occurs in the Central UKM University of Jember will be a delay in the absorption of the budget. This problem certainly has an impact on funds used temporarily to meet pre-event needs. Even more so if the funds needed are large. In addition, this delay in budget absorption also results in suboptimal activities carried out and has an impact on the University of Jember, specifically related to one of the principles of GUG (Good University Governance), namely the principle of responsibility which indicates the extent to which the process of providing public services carried out by Jember University, is it already in accordance with administrative and organizational requirements that are true and in accordance with statutory regulations. This research is qualitative research using ethnomethodology study methods. The results showed that the cause of the delay in budget absorption was due to the delay in the submission of TOR, unpreparedness in the implementation of SIMAWA, the existence of a long bureaucratic process plus a clash of busyness from the approval party, delay in SPJ collection, accumulation of activity programs at the end of the year, and the number of activity programs proposed by Central UKM of Jember University.Keywords: Public Sector Accounting, Budget Absorption, Good University Governance (GUG) ABSTRAKPenelitian ini bertujuan untuk menelaah dan menelisik secara mendalam tentang penyebab keterlambatan penyerapan yang terjadi pada UKM Pusat Universitas Jember. Penelitian ini berawal dari adanya keresahan fenomena yang terjadi pada UKM Pusat Universitas Jember akan keterlambatan dalam penyerapan anggaran. Adanya permasalahan ini tentu saja berdampak pada dana-dana yang digunakan sementara untuk memenuhi kebutuhan pra acara. Terlebih lagi jika dana yang dibutuhkan dalam nominal yang besar. Selain itu keterlambatan penyerapan anggaran ini juga mengakibatkan tidak optimalnya kegiatan yang dilaksanakan serta berdampak pada Universitas Jember, khsusunya terkait dengan salah satu prinsip GUG (Good University Goververnance) yaitu prinsip responsibilitas yang menunjukkan sejauh mana proses pemberian pelayanan publik yang dilakukan oleh Universitas Jember, apakah sudah sesuai dengan ketentuan-ketentuan administrasi dan organisasi yang benar dan sesuai dengan peraturan perundang-undangan. Penelitian ini merupakan penelitian kualitatif menggunakan metode studi etnometodologi. Hasil penelitian menunjukkan bahwa penyebab keterlambatan penyerapan anggaran dikarenakan keterlambatan dalam pengajuan TOR, ketidaksiapan dalam penerapan SIMAWA, adanya proses birokrasi yang panjang ditambah benturan kesibukan dari pihak approval, keterlambatan pengumpulan SPJ, penumpukan program kegiatan di akhir tahun, dan banyaknya program kegiatan yang diusulkan oleh UKM Pusat Universitas Jember.Kata kunci: Akuntansi Sektor Publik, Penyerapan Anggaran, Good University Governance (GUG)